Exclusive Breastfeeding and the Risk of Complicated Pneumonia in Toddlers: A Literature Review - Puja Rizkina Angelita; Wayan Sulaksmana Sandhi Parwata; Titi Pambudi Kurniawaty (Medical and Health Journal, 2026)
Pneumonia is a leading cause of morbidity and mortality in children under five worldwide. The World Health Organization (WHO, 2019) reports that pneumonia accounts for approximately 14% of all infant deaths, with more than 740,000 deaths per year. In Indonesia, the prevalence of pneumonia in infants remains high, including in West Nusa Tenggara Province, which recorded 32,128 cases in 2023, with 4,183 cases in West Lombok Regency. One protective factor believed to reduce the risk of pneumonia is exclusive breastfeeding during the first six months of life. Breast milk contains various immunological components such as secretory immunoglobulin A (sIgA), lactoferrin, lysozyme, and oligosaccharides, which play a role in protecting against lower respiratory tract infections (Lyons et al., 2020; Moraes-Pinto et al., 2021). This literature review was compiled using a narrative literature review method using relevant national and international sources, including journals from PubMed, ScienceDirect, and official WHO and UNICEF reports. The literature reviewed was published between 2015 and 2024, focusing on the relationship between exclusive breastfeeding and the incidence of pneumonia in toddlers. The analysis was conducted descriptively and thematically, reflecting the content of previous studies. Based on the study results, exclusive breastfeeding has been shown to have a significant protective effect against the incidence of pneumonia. Infants who are not exclusively breastfed have a two to five times higher risk of developing lower respiratory tract infections (Popovsky, E.Y. and Florin, T.A., 2021). A global study by Victora et al. (2016) found that exclusive breastfeeding reduces the risk of severe pneumonia by up to 64% and has the potential to prevent 820,000 child deaths annually. However, the incidence of complicated pneumonia is also influenced by other factors such as nutritional status, basic immunizations, exposure to cigarette smoke, and home environmental conditions (Dean & Florin, 2018; Saunders, 2017). Exclusive breastfeeding plays a crucial role in preventing pneumonia in toddlers through immunological mechanisms and protection of the respiratory mucosa. However, because pneumonia is a multifactorial disease, the effectiveness of exclusive breastfeeding needs to be supported by improved nutritional status, immunization coverage, and environmental improvements. Comprehensive promotive and preventive efforts are needed to reduce the incidence of pneumonia and its complications in the community.